ANALISA PENGUJIAN MESIN LAS SMAW BENGKEL MEKANIK POLITEKNIK MANUFAKTUR NEGERI BANGKA BELITUNG - Muhamad Hafiz; Sugiyarto Sugiyarto; Somawardi Somawardi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
SMAW (Shield Metal Arc Welding) welding is a welding process by joining two or more metal materials using a wrapped electrode as heat energy to melt the material. In this study, the SMAW welding machine was tested at the Polman Babel mechanical workshop to determine the difference (difference) between the current output value of the welding machine and the value indicated by the measuring instrument during welding. Then the deviation number is compared with the permissible current tolerance using the British Standard BS 7570:2000 reference standard, which is 10%. Welding machines that will be tested are 2 models, namely ewm pico 300 and Miller gold star 402 as many as 6 pieces. This research uses St37 steel and the current variations used are 75A, 150A and 225A on the ewm pico 300 and 99A, 198A, and 270A on the miller gold star 402 engine. within the tolerance limit where the largest deviation is found in machine 2 setting 75A, which is 7.46%. On the miller gold star 402 machine, there are 2 machines showing current deviations that are outside the permissible tolerances, which at engine 2 settings 198A and 270A are 16.4% and 10.9%, engine 3 all currents are 19.7%, 19 ,1%, 16,2%.